Prevalence of thyroid autoantibodies in patients with systematic autoimmune rheumatic diseases. Cross-sectional study - Posselt, Rayana Taques; Coelho, Vinícius Nicolelli; Pigozzo, Danieli Cristina; Guerrer, Marcela Idalia; Fagundes, Marília da Cruz; Nisihara, Renato; Skare, Thelma Larocca (São Paulo Medical Journal, 2017)
BACKGROUND: Thyroid autoimmunity is more common in patients with rheumatic diseases than in healthy populations. The degree of association seems subject to influence from patients’ geographical location. Here, we aimed to ascertain the prevalence of thyroid autoantibodies in a cohort of patients with systemic rheumatic disease and the degree of association between its presence and inflammatory activity. DESIGN AND SETTING: Cross-sectional observational study in a rheumatology unit. METHODS: 301 patients with systemic lupus erythematosus (SLE), 210 with rheumatoid arthritis (RA), 58 with scleroderma (SSc) and 80 with spondyloarthritis (SpA) were studied regarding thyroid function (TSH and T4), anti-thyroglobulin (TgAb) and anti-thyroperoxidase (TPOab) and compared with 141 healthy controls. Disease activity in patients with rheumatic disease was assessed through appropriate indexes. RESULTS: There were more antithyroid antibodies in SLE patients with hypothyroidism (P = 0.01; odds ratio, OR 2.7; 95% confidence interval, CI: 1.20-6.26) and in those without hypothyroidism (P = 0.06; OR 2.4; 95% CI: 1.28-4.55) than in controls. SSc patients also showed P = 0.03 both with antithyroid antibodies and hypothyroidism (OR 3.4; 95% CI: 1.06-10.80) and without hypothyroidism (OR 3.1; 95% CI: 1.11-0.13). RA and SpA patients had the same prevalence as controls (P not significant). Presence of autoantibodies with and without hypothyroidism was not associated with the activity or functional indexes evaluated. CONCLUSION: SLE and SSc were associated with higher prevalence of thyroid autoantibodies in patients with and without hypothyroidism, unlike SpA and RA. There was no link between thyroid autoantibody presence and disease activity or functional impairment.